Preliminary analysis of the efficacy of Mohs micrographic surgery combined with photodynamic therapy in a case of noninvasive extramammary Paget’s disease - Le Han; Yuchen Jiang; Miaojian Wan (Journal of Dermatological Treatment, 2024)
Purpose To evaluate the efficacy of Mohs micrographic surgery (MMS) combined with photodynamic therapy (PDT) in treating non-invasive extramammary Paget’s disease (EMPD).Materials and methods A 77-year-old male patient with non-invasive EMPD was treated with MMS followed by PDT. Preoperative fluorescence localization using 5-aminolevulinic acid (ALA) was performed to determine the surgical scope. MMS was conducted under lumbar anesthesia with intraoperative frozen-section pathology. Postoperative PDT was administered weekly for three sessions.Results The patient achieved negative surgical margins after two rounds of intraoperative pathology. Postoperative follow-up over two years showed no recurrence, and the patient did not experience significant adverse reactions.Conclusion The combination of MMS and PDT was effective in treating non-invasive EMPD, demonstrating favorable clinical outcomes and no recurrence over the two-year follow-up period.